Hard machining, glaze firing and hydrofluoric acid etching: Do these procedures affect the flexural strength of a leucite glass-ceramic? - Fraga, Sara; Valandro, Luiz F.; Bottino, Marco A. [UNESP]; May, Liliana G. (Elsevier B.V., 2015)
Objective. To evaluate the effects of hard machining, glaze firing and hydrofluoric acid etching on the biaxial flexural strength and roughness of a CAD/CAM leucite glass-ceramic; to investigate if ceramic post-machining surface roughness is influenced by the machining order and by the pair of burs used for it.Methods. A hundred forty four discs were machined by six nominally identical pairs of burs and divided into groups (n = 24): (1) machining-M, (2) machining and glaze firing-MG, (3) machining and hydrofluoric acid etching-MA, (4) machining, glaze firing and hydrofluoric acid etching-MGA, (5) machining followed by polishing, as a control-MP, (6) machining, polishing and hydrofluoric acid etching-MPA. The roughness after each treatment (R-a, and R-z) was measured. The discs were submitted to a piston-on-three ball flexure test (ISO 6872/2008) and strength data analyzed through Weibull statistics (95% CI).Results. M resulted in lower characteristic strength (sigma(0)) (128.2 MPa) than MP (177.2 MPa). The glaze firing reduced sigma(0) (109 MPa), without affecting roughness. Hydrofluoric acid etching increased the roughness without affecting sigma(0) Spearman's coefficient (r(s)) indicated strong and significant correlation between machining order and roughness (r(s)R(a) = -0.66; r(s)R(Z), = -0.73). The ceramic post-machining surface roughness differed significantly according to the pair of burs employed (p < 0.05).Significance. hard machining and glaze firing reduced the leucite ceramic strength, while hydrofluoric acid etching did not affect the strength. Variability in the roughness might be expected after machining, since it was influenced by the machining order and by the bur pairing. (C) 2015 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Machining; Leucite glass-ceramic; CAD/CAM; Hydrofluoric acid etching; Glaze firing; Biaxial flexural strength